2021
DOI: 10.1111/ijsa.12354
|View full text |Cite
|
Sign up to set email alerts
|

Examining the situational antecedents of interview faking behavior: A qualitative study

Abstract: Over a decade has passed since the development of Levashina and Campion's (2006) Model of Faking Likelihood in Employment Interviews. Although researchers have accumulated considerable knowledge about interview faking, this literature may benefit from a deeper understanding of certain areas such as the situational antecedents of this behavior. As such, we conducted nine focus groups with Canadian participants to explore this research question. An inductive thematic analysis of these focus group data yielded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
4
1
Order By: Relevance
“…Concerning the possible effects of a personable interviewer on faking intentions, an empirical test revealed a null effect. This is in contrast to Study 1 and to the qualitative study by Ho et al (2021) that found that a friendly interviewer reduced interview anxiety and therefore the probability of faking. A reason why we did not find any effect could be that participants could not perceive any interview anxiety due to the hypothetical scenario and thus an interviewer described as personable had no impact on faking intentions.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…Concerning the possible effects of a personable interviewer on faking intentions, an empirical test revealed a null effect. This is in contrast to Study 1 and to the qualitative study by Ho et al (2021) that found that a friendly interviewer reduced interview anxiety and therefore the probability of faking. A reason why we did not find any effect could be that participants could not perceive any interview anxiety due to the hypothetical scenario and thus an interviewer described as personable had no impact on faking intentions.…”
Section: Discussioncontrasting
confidence: 96%
“…Furthermore, the qualitative answers from the open-ended questions in Study 1 also revealed a surprising result that was not predicted by any of the current faking models (e.g., Levashina & Campion, 2006;McFarland & Ryan, 2000Roulin, Krings & Binggeli, 2016). However, Ho et al (2021) found similar results in a recent qualitative study. In our study, nearly 20% of the answers indicated that a personable interviewer would prevent participants from faking in an interview.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations